Trends in Naming System on Javanese Society: A Shift From Javanese to Arabic - Aribowo, Eric Kunto; Herawati, Nanik (Lingua Cultura, 2016)
Personal names could be used to trace a person’s socio-historical background, including ethnic identity. Traditionally the Javanese people named their children using the Javanese language. Later, the phenomenon showed there was a new trend in naming. Arabic began to massively adopted as the elements in the personal name. This paper aimed to describe the trend of the naming system on Javanese people which beginning to switch from the Javanese to Arabic. This article used corpus data method. Data obtained from the Javanese people name corpus of data Administration System (SIAK) administered by the Civil Registry Service Office in Klaten, Jawa Tengah. The Arabic name then compared with the Javanese to determine the differences in naming system and it’s reference. The results show there is a huge number of Arab intergenerational name. Modern parents tend to name their children using Arabic words. These efforts are deployed in actualizing self-identify as a Muslim. The Javanese people now prefer to highlight their identity as part of Moslems than the Javanese.